2020
DOI: 10.1002/cncr.33101
|View full text |Cite
|
Sign up to set email alerts
|

Functionally impactful TP53 mutations are associated with increased risk of extranodal extension in clinically advanced oral squamous cell carcinoma

Abstract: BACKGROUND: The treatment of advanced oral squamous cell carcinoma (OSCC) is a clinical challenge because it is unclear which therapeutic approaches are the best for this highly heterogeneous group of patients. Because TP53 mutations are the most common genetic event in these tumors, the authors investigated whether they could represent an ancillary biomarker in the management of advanced OSCC. METHODS: The TP53 gene was sequenced in 78 samples from patients with advanced OSCC who received treatment at 2 insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…However, several ENEs are overlooked during clinical examinations due to limited radiological accuracy and the absence of a critical predictor of ENE. Recent studies have shown that TP53 mutation and SERPINE1 expression in fibroblasts increase the risk of ENE [ 40 , 41 ]. However, their abilities as predictors of ENE are limited, and the evaluation of these factors is difficult in routine work [ 40 , 41 ]; thus, a versatile and more simple method for supporting the cENE evaluation and predicting the presence of ENE using biopsy or surgically resected specimens of OSCC is required.…”
Section: Discussionmentioning
confidence: 99%
“…However, several ENEs are overlooked during clinical examinations due to limited radiological accuracy and the absence of a critical predictor of ENE. Recent studies have shown that TP53 mutation and SERPINE1 expression in fibroblasts increase the risk of ENE [ 40 , 41 ]. However, their abilities as predictors of ENE are limited, and the evaluation of these factors is difficult in routine work [ 40 , 41 ]; thus, a versatile and more simple method for supporting the cENE evaluation and predicting the presence of ENE using biopsy or surgically resected specimens of OSCC is required.…”
Section: Discussionmentioning
confidence: 99%
“…These predictive factors could be simply evaluated using routine H&E staining and included in pathology reports. Few studies have examined the pathological predictive factors for ENE [40,41]. Gleber-Netto et al noted an increasing trend toward the frequency of ENE among patients with TP53mutant OSCC (65.5%) than among those with WT TP53 OSCC (42.1%; p=0.07) [40].…”
Section: Discussionmentioning
confidence: 99%
“…However, several ENEs are overlooked during clinical examinations due to limited radiological accuracy and the absence of a critical predictor of ENE. Recent studies have shown that TP53 mutation and SERPINE1 expression in broblasts increase the risk of ENE [40,41]. However, their abilities as predictors of ENE are limited, and the evaluation of these factors is di cult in routine work [40,41]; thus, a versatile and more simple method for supporting the cENE evaluation and predicting the presence of ENE using biopsy or surgically resected specimens of OSCC is required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have shown the possible association of TP53 gene polymorphism in oral, breast, bladder, colorectal and lung cancers (Soulitzis et al, 2002;Katiyar et al, 2003;Zhu et al, 2007;Rivlin et al, 2011;Hanel and Moll 2012). TP53 mutations have shown to be associated with an increased risk of extranodal extensions in patients with advanced OSCC (Gleber-Netto et al, 2020). According to the IARC database (2018), 42.51% of head and neck cancers carry somatic mutations in TP53.…”
Section: Non-invasive Saliva-based Detection Of Gene Mutations In Oral Cancer Patients By Oral Rub and Rinse Techniquementioning
confidence: 99%